2017
DOI: 10.3727/096504016x14719078133401
|View full text |Cite
|
Sign up to set email alerts
|

miR-214-5p Targets ROCK1 and Suppresses Proliferation and Invasion of Human Osteosarcoma Cells

Abstract: MicroRNAs (miRNAs) are small conserved RNAs regulating specific target genes in posttranscriptional levels. They have been involved in multiple processes of tumor progression, including cell proliferation. miR-214-5p (also miR-214*) is a newly identified miRNA, and its functions are largely unknown. In this study, we explore the role of miR-214-5p in the proliferation and invasion of human osteosarcoma (OS) cells. The results showed that miR-214-5p was sharply reduced in OS tissues and cell lines, compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 24 publications
3
37
0
1
Order By: Relevance
“…We found miR-214-5p expression was significantly lower in HCC tissues when compared with that in matched normal tissues, which was the same as the expression status of miR-214-5p in human osteosarcoma. 32 Also, we found miR-214-5p overexpression could inhibit cell proliferation, migration, and induce cell cycle arrested in G0/G1, indicating the miR-214-5p may play a tumor suppressor role in the development and progression of HCC. Following, we identified the targeting gene of miR-214-5p in regulating cell proliferation, cell migration, and cell cycle since it is widely recognized that miRNA exerts its biological function through regulating the expression of its targets.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…We found miR-214-5p expression was significantly lower in HCC tissues when compared with that in matched normal tissues, which was the same as the expression status of miR-214-5p in human osteosarcoma. 32 Also, we found miR-214-5p overexpression could inhibit cell proliferation, migration, and induce cell cycle arrested in G0/G1, indicating the miR-214-5p may play a tumor suppressor role in the development and progression of HCC. Following, we identified the targeting gene of miR-214-5p in regulating cell proliferation, cell migration, and cell cycle since it is widely recognized that miRNA exerts its biological function through regulating the expression of its targets.…”
Section: Discussionmentioning
confidence: 67%
“…Also, we found miR‐214‐5p overexpression could inhibit cell proliferation, migration, and induce cell cycle arrested in G0/G1, indicating the miR‐214‐5p may play a tumor suppressor role in the development and progression of HCC. Following, we identified the targeting gene of miR‐214‐5p in regulating cell proliferation, cell migration, and cell cycle since it is widely recognized that miRNA exerts its biological function through regulating the expression of its targets . Therefore, by bioinformatic analysis and luciferase activity assay, we demonstrated KLF5 might be a potential target of miR‐214‐5p in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, microRNAs gain many attention for their function as gene expression regulators. Just recently, miR-214-5p has been found to influence tumor process [15]. However, the effect of miR-214-5p on HCC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in serum, Elemeery MN, et al found miR-214-5p could be considered as early biomarkers for tracking the progress of liver fibrosis to HCC [14]. Zhang, et al showed that miR-214-5p suppresses proliferation and invasion of human osteosarcoma cells by targeting ROCK1 [15]. Li et al found in osteoblastic MC3T3-E1 cells, inhibition of microRNA-214-5p promotes survival and extracellular matrix formation [16].…”
Section: Introductionmentioning
confidence: 99%